Analysis of theoretical and methodological bases of teaching object-oriented programming languages in higher school - Shayakhmetova, B.; Orumbayeva, N.; Omarova, Sh.; Antipov, Yu. (Bulletin of the Karaganda University. Mathematics Series, 2017)
One of the most urgent tasks of our time is the problem of teaching in higher education. The task of teachers is to train young people in the field of the latest computer technologies. When teaching, the teacher must also change the methodology of training specialists in higher education in an adequately changing pace of development. Recently, there has been a definite bias towards the creation of software for complex systems, the tasks under consideration are becoming much more complicated, so there are not enough old techniques and methods used earlier to create simple or formalized programs. And in this regard, we will consider in detail the paradigm of object - oriented technology, which is developing at the present time.